THE EFFECT OF OWNERSHIP CONCENTRATION AND WARRANTS PARTICIPATION TOWARDS THE LEVEL OF STOCK UNDERPRICING DURING THE INITIAL PUBLIC OFFERING ON IDX PERIOD 2019 & 2020 (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Due to the rapid rate of business development, companies require a large capital by issuing shares to the public, where in 2020 COVID-19 brings a serious impact on the world’s economic sector. This study meant to investigate the effect of ownership concentration and warrants inclusion on the level of share underpricing during the IPO (Initial Public Offering) on the Indonesia Stock Exchange in 2019 and 2020. The research population are entities registered on the Indonesia Stock Exchange and conducting IPO in 2019 and 2020, amounting to 107 companies. The method used during the selection of the sample group is the purposing sampling method. This study uses multiple linear regression analysis. The test results indicate that (1) ownership concentration has no effect on underpricing (2) the inclusion of equity has no effect on underpricing, and (3) Corona has a negative effect on underpricing. Keywords: Underpricing, Ownership Concentration, Warrant inclusion, COVID-19